Transparency and Accountability of Village Fund Allocation Management in Wironanggan, Gatak, Sukoharjo - Anim Rahmayati; Ema Tietien Chrystiana (Journal of International Conference Proceedings (JICP), 2019)
This study was aimed to analyze the effect of financial statement presentation, the accessibility of financial reports and functional supervision on transparency, and the accountability of Village Fund Allocation (ADD) management in Wironanggan, Gatak, Sukoharjo. The research method used in this research was quantitative research using primary data. It was obtained by distributing questionnaires to respondents who were the village officials of Wironanggan, Gatak, Sukoharjo, the neighbourhood (RT), the hamlet (RW) and the society which was 78 respondents. Data analysis techniques used was multiple linear regression analysis. The result of this study based on data analysis result was that the presentation of accountability report and accessibility did not affect the transparency of village funds management in Wironanggan, whereas the functional supervision had a considerable positive effect on transparency in village fund management. In addition, the results of the study also pointed out that the presentation of accountability report had a significant positive effect on the accountability of village fund management, while the accessibility and functional supervision did not affect the accountability of village fund management.